Ethik und Ästhetik: die dornige Frage nach Moral und Freiheit - Martinelli, Monica (Simmel Studies)

(untitled) (Edizioni ETS, 2024)
The relationship between morality and freedom is present throughout Simmel's intellectual path. Significantly, the topic ‘freedom’ is treated in one of Simmel's first works specifically dedicated to moral science. Within the framework of his sociology and philosophy of life as well as his anthropological vision, Simmel rethinks the Kantian categorical imperative: on the one hand, developing his own 'moral principle of freedom' and, on the other, carrying out an inversion of the Kantian imperative whereby what had been understood as universal, valid for all individuals and capable of guiding their actions, becomes an individual law whose moral imperative is particular to each individual and universally affects all that individual's actions. Morality concerns the whole human being and coincides with the response – that is, responsibility - in relation to life, beyond dualistic visions that separate what is related (e.g., bond and freedom, reason and sensitivity, objective and subjective, etc.): on this point, the ethical dimension and freedom intertwine the aesthetic dimension, capable of restoring the integrity of human existence and experience. Aesthetics, in Simmel, has to do with the feeling of a profound intensity of life, offering the possibility of a connection between the experience of perception and sensitive affection with the knowledge of life from inside. This involves the authenticity of the individual, leading him to feel the reality of life to which he can respond. And freedom rests on this response, which is responsibility.